Prevalence of immune-mediated inner ear disease in non-segmental vitiligo: A cross-sectional study - Marchioro, Helena Zenedin (2023)
Background: Sensorineural hearing loss (SNHL) is associated with non-segmental vitiligo (NSV); however, the aetiology of SNHL has not been explored. The concomitance of autoimmune disease in vitiligo patients demands the investigation of immune-mediated inner ear disease (IMIED) as a cause of SNHL in NSV. The anti-Hsp70 antibody is a serological marker of IMIED, which may help in the early diagnosis of this disease. Objective: To evaluate the prevalence of IMIED in NSV patients. Methods: Cross-sectional study involving NSV adult patients and a control group, evaluated through audiometry and serological dosage of the anti-Hsp70 antibody. Results: In total, 112 cases and 23 controls were evaluated. Bilateral SNHL was found in 28 (25.0%; 95%CI 17.9%–32.1%) patients and in 1 (4.3%) control (p = 0.019). Six cases (5.4%; 95%CI 2.7%–8.0%) presented bilateral SNHL of unexplained aetiology, and anti-Hsp70 antibody positivity, fulfilling the diagnostic criteria for IMIED. No controls met the diagnostic criteria for IMIED. Serum anti-Hsp70 antibodies were higher in cases with IMIED: median 220.9 vs. 85.1 ng/ml (p = 0.001). Conclusion: The prevalence of IMIED is remarkable in NSV adult patients.